Endophthalmitis after cataract surgery despite intracameral antibiotic prophylaxis with licensed cefuroxime. Issue 9 (September 2016) - Mesnard, Charles; Beral, Laurence; Hage, Rabih; Merle, Harold; Farès, Selim; David, Thierry
Abstract : Purpose : To report a case series of post‐phacoemulsification endophthalmitis despite antibiotic prophylaxis with an intracameral injection of a licensed cefuroxime formulation (Aprokam). Setting : University Hospitals of Pointe‐à‐Pitre, Guadeloupe, and Fort‐de‐France, Martinique, French West Indies. Design : Retrospective case series. Methods : Patients who had cataract surgery with licensed cefuroxime prophylaxis between March 1, 2013, and July 31, 2015, and developed endophthalmitis were included. Bacteriologic findings and final corrected distance visual acuity 6 months after treatment were collected. Results : Five patients developed endophthalmitis within 15 days after surgery, which was performed in different settings by different cataract surgeons. All patients had no‐stich cataract surgery. Surgery was uneventful in 4 cases. One patient had a posterior capsule rupture. An anterior chamber paracentesis with analysis of the aqueous humor was performed to confirm endophthalmitis. Bacteriologic tests showed α‐hemolytic streptococcus in 2 cases, Staphylococcus epidermidis in 1 case, and Serratia marcescens in 1 case. Two strains of bacteria showed cefuroxime resistance on the antibiogram. Despite parenteral and intravitreal injections of antibiotics, 4 of 5 cases had a poor outcome, with a visual acuity of less than 20/200. Retinal detachment (RD) was the most frequent complication observed in the following months. Conclusions : Although licensed cefuroxime has proven to be efficient in reducing the incidence of endophthalmitis, it has not eradicated this potentially severe complication of cataract surgery. Endophthalmitis occurring after the use of licensed cefuroxime can still result in very poor visual outcomes related to the infection itself or to its delayed complications such as RD. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.